THE URGENCY OF MARRIAGE REGISTRATION IN THE PERSPECTIVE OF INDONESIAN MARRIAGE LAW AND ISLAMIC LAW - Sulfian, A. Sultan (Jurnal Al-Dustur, 2023)
This research aims to analyze and explain the urgency of registering marriages in the perspective of Indonesian marriage law and Islamic law, as well as the legal consequences of marriages that are not registered according to Indonesian marriage law and Islamic law. This research is a normative legal research or doctrinal legal research (doctrinal approach), namely legal research that uses secondary data sources which are carried out by approaching legal norms or substances, legal principles, legal theory, legal arguments and legal comparisons with data collection techniques, namely through careful observation and tracing of various legal materials, namely tracing primary legal materials, secondary legal materials, and tertiary legal materials.The results of this research show that the urgency of registering the marriage can be seen from various perspectives. Even though there is still ambiguity regarding the provisions for registering marriages in the Marriage Law, the requirement for registration of marriages is intended within the framework of the state's function of providing guarantees of protection and legal certainty. Meanwhile, from the perspective of Islamic law, the registration of marriages has reached a "daruriyah" condition where marriages that are not recorded will cause a lot of loss and harm to the parties in the marriage. So substantially there is no conflict between Indonesian marriage law and Islamic law, both of them are the same in view of the urgency of registering marriages that registration of marriages cannot be separated from the implementation of the marriage itself. Furthermore, marriages that are not registered will have very detrimental consequences for the husband, wife, children, and assets in the marriage which have a negative impact both from a juridical, sociological, and psychological aspect.Â